Construcción y evaluación de una tobera a escala menor basada en material compuesto para cohetes de órbita baja (2013)
A method for minor scale manufacturing of nozzle prototype for low orbit rockets based on low cost composite materials was developed, using as methodology a nozzle material design conformed by a thermal zone and structural zone. For the thermal zone, a composite particulate material based on a reinforced polymeric matrix with ceramic powder, silicon carbide, and type 2 ceramic was used, which was prepared by a process of molding, casting and compaction, after the manufacturing of the thermal zone al laminating process of a fibroreinforced material with netting of glass fiber and carbon fiber was done. In the nozzles, the performance of the used materials through simulation of actual operation conditions was evaluated, where thermal and structural test were involved, such as: traction tests, pressure loads simulation with a specialized software, and impact by oxy flame test to determine the weight loss, the thickness and the differential temperature. The obtained results showed the effective behavior of the system for 60 seconds of flight using a particulate composite material with 70% of type 2 ceramic and 30% of polymeric material for the thermal zone and configuration glass fiber matt of 225 g/m2 – glass fiber Voland 320 g/m2 tilted 0º - glass fiber matt of 225 g/m2 – carbon fiber tilted 0º